2010
DOI: 10.1111/j.1438-8677.2009.00291.x
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell death during pigment gland formation in Gossypium hirsutum leaves

Abstract: Ultrastructural studies have shown that the formation of pigment glands in Gossypium hirsutum L. leaves is a lysigenous process, originating from a cluster of cells in the ground meristem. Various techniques were used here to investigate whether programmed cell death (PCD) plays a critical role in this developmental process. Nuclei of internal cells in the pigment gland-forming tissue were TUNEL-positive and DAPI-negative, suggesting that DNA cleavage is an early event and complete DNA degradation is a late ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 33 publications
2
27
0
Order By: Relevance
“…Most of the time, the DNA electrophoresis did not show ‘ladders’ during the PCD process in plants, rather it showed a DNA smear of a size ranging from approximately 180 bp to genomic DNA. This was reported during aerenchyma formation in T. angustifolia (Ni et al ), laticiferous canal formation of Decaisnea fargesii fruits (Zhou and Liu ), pigment gland formation in G. hirsutum leaves (Liu et al ) and perforation formation of M. obliqua and lace plant leaves (Gunawardena et al , ). Occasionally, a DNA ladder of approximately 180 bp and multimers has been detected in endosperm development of maize (Young and Gallie ), aerenchyma formation induced by ethylene of hypoxia in roots of maize (Gunawardena et al ), procambium and ground meristem of P. sativum root tips exposed to flooding (Gladish et al ) and heat shock‐induced PCD in mung bean seedlings (Egorova et al ).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Most of the time, the DNA electrophoresis did not show ‘ladders’ during the PCD process in plants, rather it showed a DNA smear of a size ranging from approximately 180 bp to genomic DNA. This was reported during aerenchyma formation in T. angustifolia (Ni et al ), laticiferous canal formation of Decaisnea fargesii fruits (Zhou and Liu ), pigment gland formation in G. hirsutum leaves (Liu et al ) and perforation formation of M. obliqua and lace plant leaves (Gunawardena et al , ). Occasionally, a DNA ladder of approximately 180 bp and multimers has been detected in endosperm development of maize (Young and Gallie ), aerenchyma formation induced by ethylene of hypoxia in roots of maize (Gunawardena et al ), procambium and ground meristem of P. sativum root tips exposed to flooding (Gladish et al ) and heat shock‐induced PCD in mung bean seedlings (Egorova et al ).…”
Section: Discussionmentioning
confidence: 74%
“…The same phenomenon was also observed in other species, such as T. angustifolia (Ni et al ) and lace plant (Wertman et al ). In addition, membrane‐bound structures were also noted during pigment gland formation in Gossypium hirsutum (Liu et al ) and aerenchyma formation in Zea mays (Gunawardena et al ). Following organelle degradation, the collapse of plasma membrane and emergence of secondary vacuoles were observed in pre‐cavity cells at the cavity expansion phase (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Dangl et al (2000) suggested that the lysigenous formation of glandular cells may be a PCD phenomenon. This has been confirmed by Liu et al (2010) studying the lysis of pigment gland formation in Gossypium hirsutum, and the lysigenous formation of laticiferous canals in Decaisnea fargesii . Chen and Wu (2010), having studied schizolysigenous formation of the secretory cavity in Citrus sinensis, also consider it a PCD process.…”
Section: Introductionmentioning
confidence: 59%
“…They are also evident in the formation of the trichome-like cavity of D. dasycarpus. Bringing together these ultrastructural characteristics suggest patterns of autophagy and autolysis (Gaffal et al, 2007;Herman and Lamb, 1992;Hoh et al, 1995;Liu et al, 2010;Robinson et al, 1998).…”
Section: Hallmarks Of Programmed Cell Death (Pcd)mentioning
confidence: 99%
See 1 more Smart Citation